Clinical potential of canagliflozin in cardiovascular risk reduction in patients with type 2 diabetes - Skelley JW; Carter BS; Roberts MZ (Vascular Health and Risk Management, 2018)
Jessica W Skelley, Brooke S Carter, Megan Z Roberts Department of Pharmacy Practice, McWhorter School of Pharmacy, Samford University, Birmingham, AL, USA Abstract: Cardiovascular disease is the leading cause of morbidity and mortality among patients with diabetes mellitus, as well as the leading diabetes-associated health care cost. The prevalence and associated impact of cardiovascular disease among those with diabetes engenders the need to identify cardiovascular effects of antihyperglycemic agents. This review seeks to evaluate the impact of canagliflozin, a SGLT2 inhibitor, on cardiovascular risk factors and outcomes. The 14 published trials to-date exploring various cardiovascular risk factors and outcomes among patients receiving canagliflozin were identified and included within the review. Overall these studies demonstrate that among patients with type 2 diabetes mellitus, canagliflozin results in decreased systolic and diastolic blood pressure, lower body weight, and also exhibits reno-protective effects. These findings were similar when canagliflozin was compared to placebo or other antihyperglycemic agents and explored among subsets such as those with chronic kidney disease. In addition, findings from the three trials exploring cardiovascular outcomes of canagliflozin included reduction in cardiovascular mortality and lower incidence of heart failure-associated hospitalizations. Results from studies including other SGLT2 inhibitors suggest that cardiovascular benefits are likely a class-effect found among current SGLT2 inhibitors. Continued research specific to canagliflozin is needed to clarify risks of adverse effects and determine optimal dosing requirements for canagliflozin in regard to cardiovascular risk reduction. Keywords: antihyperglycemic, sodium-glucose co-transporter 2 inhibitors, cardiovascular disease, diabetes mellitus